THE SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN BIDAN DESA BARU DEGAN METODE SMART DI UPT PUSKESMAS PELANGAN LOMBOK BARAT: SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN BIDAN DESA BARU DEGAN METODE SMART DI UPT PUSKESMAS PELANGAN LOMBOK BARAT - Muhammad Arfan; Putri T Prasetyaningrum (LPPM Universitas Widya Dharma, 2022)
UPT public health center is a health center in the western sekotong area that serves people in remote villages. Some health centers in West Lombok have problems with village midwives. In a puskesmas, village midwives only survive working for a short time, often mistakes are made when receiving village midwives by the puskesmas, after working it turns out that the village midwife does not meet the appropriate criteria or does not have the necessary special abilities. Puskesmas will be needed. The Puskesmas will be assisted by the DLUD (regional public service agency) to open job vacancies or accept new village midwives to fill the puskesmas polindes when the puskesmas has a village midwife whose contract period is about to expire. In the technical implementation unit (UPT) of the customer health center, the process for accepting village midwives is still manual, because there is no system to assess prospective village midwives in the process of accepting village midwives at the customer health center, there are many obstacles. These problems can be fixed by building a decision support system that helps administration in decision making by determining several criteria, namely education, certificates, age, and length of work needed and speeding up the workings of the puskesmas administration to accept new village midwives so as to produce a plan. decision support system for the acceptance of new village midwives. Therefore, this research is entitled